Regional disparities in SRM impacts: the challenge of diverging preferences - Heyen, Daniel; Wiertz, Thilo; Irvine, Peter James (Climatic change, 2015)
Solar radiation management (SRM) has been proposed as a potential method for reducing risks from global warming. However, a widely held concern is that SRM will not reverse the climate consequences of global warming evenly, resulting in regional disparities in the combined climate response to elevated greenhouse gas (GHG) concentrations and SRM. Recent research has used climate model projections to quantitatively assess how regional disparities affect the overall efficiency of global SRM and what the resulting potential for cooperation and conflict with regard to SRM may be. First results indicate that regional disparities, although present, may not be severe. These assessments rest on the assumption that, for all regions, any deviation from a past climate state inflicts damages. We challenge this strong change-is-bad assumption by showing that diverging preferences are not only plausible, but may also have the potential to substantially alter assessments of regional disparities. We argue that current assessments yield little information on the ethical and political implications of SRM and that diverging preferences should receive more attention. Promising directions for future inquiry include bridging gaps to the general climate impact research and to research on the social implications of environmental change.
Gesehen am 31.08.2020